A comparison of dental health care attitudes in the Netherlands in 1985, 1995, and 2001 - Bos A, Hoogstraten J, Prahl-Andersen, B. (Blackwell Synergy, 2003)
The aim of the present study was to re-establish and update empirical data obtained in 1985 and 1995 using the dental attitudes questionnaire (DAQ).